A quantitative analysis of investor over-reaction and under-reaction in the South African Equity Market : a mathematical statistical approach - Mbonda Tiekwe, Aude Ines (Stellenbosch : Stellenbosch University, 2022)
Thesis (PhD)--Stellenbosch University, 2022.